Strengthening Entrepreneurship: Sharia Empowerment for MSMEs Amidst the Covid-19 Pandemic - Ramadhani Irma Tripalupi; Prameshwara Anggahegari (Research Synergy Foundation, 2022)
This study aims to explain the strengthening of entrepreneurship based on sharia empowerment for micro, small and medium enterprises (MSMEs) in dealing with the impact of the Covid-19 pandemic. This research focuses on three things: 1) Indonesian MSMEs, 2) Moslem entrepreneurship, and 3) Sharia empowerment. Using qualitative approaches, descriptive methods, and exploratory analysis, this research tries to provide the rationale for strengthening MSMEs using the spectacle of sharia empowerment amidst the pandemic. Despite the halt of business operations in this pandemic, we found that many MSMEs, which are home-based businesses, have sprung up but need an empowerment process to survive and thrive. This condition is seen as a major challenge for sharia empowerment programs. This paper provides a conceptual framework to understand how sharia empowerment can strengthen the MSMEs. However, this research has some limitations, one of which is the inability to validate the findings directly; therefore, we encourage further research to cover these matters.